Гендерна культура студентської молоді в умовах закладу вищої освіти - Шлєіна, Людмила Іванівна; Шлеина, Людмила Ивановна; Shlieina, Liudmyla (My University, 2018)
UK: У статті розкрито сутність та особливості гендерної культури як теоретичне підґрунтя її формування у студентської молоді. Проаналізовано стан дослідженості проблеми формування гендерної культури студентської молоді в умовах закладу вищої освіти; констатовано, що найбільший інтерес науковців викликає проблема гендерного виховання молоді. У дослідженні з’ясовано, що поняття «гендерна культура» у науковій літературі розглядається як сукупність статево-рольових цінностей у суспільних відносинах і відповідних до них норм поведінки, потреб, інтересів та форм діяльності, що зумовлена суспільним устроєм, релігійними віруваннями. Доведено, що молодий студентський вік є чутливим і сприятливим періодом для формування гендерної культури. EN: In the article the essence and special aspects of gender culture as theoretical basis of its formation among young students are explained. The state of the problem of young student gender culture formation in conditions of a higher education institution is analyzed. It was stated that the greatest interest of scientists is the problem of young people gender education. The research found that the concept of "gender culture" in the scientific literature is regarded as a complex of gender-role values in social relations and their corresponding norms of behavior, needs, interests and forms of activity, which is conditioned by social order, religious beliefs. It is proved that the young student's age is a sensitive and favorable period for the gender culture formation The entry of Ukraine into the world educational space has led to the need for the implementation of a new educational system, which requires new approaches, relationships, behavior, etc. An integrated solution of the society sustainable development problems is impossible without creating equal opportunities for self-realization of the individual regardless of its gender in any sphere of life. An indicator of a truly democratic society is the realization of the idea of gender equality in interpersonal relations, giving representatives of both genders equal rights and equal chances. Recently, the issue of gender equality has become a priority in the whole modern world, there has been an urgent need for the formation of new relationships between women and men, which should be based on equal partnership, giving both genders equal access to the benefits of civilization. It is determined that gender culture of young students is a subjectively determined system of values, gender knowledge, gender-role norms of behavior that promote the implementation of student abilities of different genders as equal social creatures, form the gender qualities of the individual through the implementation of such organizational and pedagogical conditions as development gender competence of the teacher; the organization of gender education of students in the educational activities of the higher education institution.
Keywords: гендерна культура; гендер; культура; студентська молодь; gender culture; gender; culture; young students